Impact of Sunlight on the Age of Onset of Bipolar Disorder (2012)
ABSTRACT: Objective: Although bipolar disorder has high heritability, the onset occurs during several decades of life, suggesting that social and environmental factors may have considerable influence on disease onset. This study examined the association between the age of onset and sunlight at the location of onset. Method: Data were obtained from 2414 patients with a diagnosis of bipolar I disorder, according to DSM-IV criteria. Data were collected at 24 sites in 13 countries spanning latitudes 6.3 to 63.4 degrees from the equator, including data from both hemispheres. The age of onset and location of onset were obtained retrospectively, from patient records and/or direct interviews. Solar insolation data, or the amount of electromagnetic energy striking the surface of the earth, were obtained from the NASA Surface Meteorology and Solar Energy (SSE) database for each location of onset. Results: The larger the maximum monthly increase in solar insolation at the location of onset, the younger the age of onset (coefficient= −4.724, 95% CI: −8.124 to −1.323, p = 0.006), controlling for each country’s median age. The maximum monthly increase in solar insolation occurred in springtime. No relationships were found between the age of onset and latitude, yearly total solar insolation, and the maximum monthly decrease in solar insolation. The largest maximum monthly increases in solar insolation occurred in diverse environments, including Norway, arid areas in California, and Chile. Conclusion: The large maximum monthly increase in sunlight in springtime may have an important influence on the onset of bipolar disorder.